The Paradox of Connectivity Justice: The Hegemony of Splitsing and Fragmentation of Criminal Liability in Civilian-Military Mixed Criminal Cases - Prastopo Prastopo; Jelli Rita; Ahmad Jaeni; Sugianor Sugianor (Lembaga Teewan Journal Solutions, 2026)
Connectivity justice is designed as an integrative mechanism for adjudicating criminal offences jointly committed by legal subjects falling under both general and military jurisdictions. In practice, however, the splitting of case files, or splitsing, in civilian-military mixed cases may transform connectivity from a unifying procedural forum into a merely declaratory norm with limited operational force. This article examines why splitsing may negate the ratio legis of connectivity justice, particularly in relation to equality before the law, due process of law, and the unity of criminal liability. The research applies a normative juridical method with descriptive-prescriptive analytical characteristics, using statutory, conceptual, and case approaches. Legal materials are collected through library research covering legislation, court decisions, doctrine, journal articles, books, and contemporary case materials. The article argues that splitsing in mixed civilian-military cases cannot be treated as a purely technical prosecutorial instrument because it affects forum allocation, evidentiary coherence, public access, and the construction of criminal responsibility. The novelty of this article lies in proposing a “limited-priority connectivity model”, which requires a connectivity trigger test, a dominant-interest test, joint case assessment, and written reasoned justification before any case splitting may be undertaken. This model is necessary to prevent splitsing from becoming an instrument of jurisdictional fragmentation.